Gynecology Cancer in Relationship with Obesity - Rauw, Gracia M R G; Laihad, Bismarck J; Affandi, Biran (Indonesian Journal of Obstetrics and Gynecology, 2016)
Objective: To know the relationship between obesity and gynecology cancer. Method: This study use case control study design for 250 gynecology patients (125 controls and 125 cases) in Prof. Dr. R. D. Kandou Manado Hospital from 1 July to 30 November 2015. The data was collected by measuring Body Mass Index (BMI) and filing out selfadministered questioners. Result: From the 250 subjects, the study group (125 subjects), 72 subjects have obesity (57.6%) and 97 subjects have multiple parities (77.6%) with 58 subjects diagnosed with cervical cancer (46.4%). In the control group (125 subjects), 71 subjects have normal weight (56.8%) and 67 subjects have multiple parities (53.6%) with 64 subjects diagnosed with ovarium cysts (51.2%). Using multivariate logistic regression, the overweight and obese subjects have 7 folds higher risk to develop gynecology cancer compared to those with normal or underweight subjects. Those with multiple parities and grande multipara subjects have 3 folds higher risk to develop gynecology cancer compared with those who are nullipara and primipara. Conclusion: A significant correlation is found between obesity and gynecology cancer using multivariate logistic regression analysis (p=0.000, OR=6.9 (95% CI = 3.62-13.13). [Indones J Obstet Gynecol 2016; 1: 23-30] Keywords: gynecology cancer, multiple parities, obesity